2022
DOI: 10.1055/s-0042-1747947
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Knee Osteoarthritis on Spinopelvic Alignment and Global Sagittal Balance

Abstract: Osteoarthritis (OA) of the knee is thought to lead to a loss of lumbar lordosis (LL) as a compensation for knee flexion contracture. Changes in sagittal alignment are not limited to the lumbar spine and involve a complex interplay of alignment of the hip, pelvis, and spine. While spine–hip interactions have been previously explored, the influence of knee OA sagittal alignment parameters on spinopelvic alignment and global sagittal balance remains unexplored. Standing radiological examination using EOS biplanar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 20 publications
0
5
0
Order By: Relevance
“…First, despite the large amount the valgus correction, not all postoperative alignment may have achieved the large correction range of 60-65% in the tibial plateau width; second, FTA may have been influenced by other factors apart from the mechanical axis. For instance, knee flexion angle, lateral trunk tilt, muscle strength in lower limbs, and individual walking posture may also exert an influence on the FTA [26,27]. In the analysis of the postural stability, the LS-COP was positioned significantly more centered for patients after HTO, and more similar to the healthy adults.…”
Section: Discussionmentioning
confidence: 94%
“…First, despite the large amount the valgus correction, not all postoperative alignment may have achieved the large correction range of 60-65% in the tibial plateau width; second, FTA may have been influenced by other factors apart from the mechanical axis. For instance, knee flexion angle, lateral trunk tilt, muscle strength in lower limbs, and individual walking posture may also exert an influence on the FTA [26,27]. In the analysis of the postural stability, the LS-COP was positioned significantly more centered for patients after HTO, and more similar to the healthy adults.…”
Section: Discussionmentioning
confidence: 94%
“…This study found sex differences in the relationship between lumbar vertebra-pelvic and knee line of force balance in patients with limited knee osteoarthritis.Differences in coronal radiography parameters caused by genders is described in Fig. 3.In women,the deformity of knee joint was associated with backward pelvis and straightening of lumbar curvature(P<0.01),while in men, the deviation of lower limb weight axis was associated with forward pelvis(P<0.01).The difference was not signi cant in severe group(P>0.05).The reason may be that women's pelvis is relatively wide in shape, but shorter and the tension of the surrounding muscle ligaments,such as the iliolumbar ligament,is relaxed compared with that of men,resulting in different changes in pelvis backward,resulting in reduced lumbar curvature and reduced interluminal space of the knee joint [12] .Previous studies have con rmed that female LL has a positive correlation with PI,and as LL decreases, PI decreases because the line of force compensates.Katsumi et alsuggested that the reduction of lumbar lordosis in knee osteoarthritis is a compensation for knee exion contracture [13] .Sagittal alignment is not limited to the lumbar spine,but involves a complex interplay of hip,pelvic,and spinal alignment.When the lumbar lordosis Angle decreases,in order to maintain standing balance,there will be pelvic tilt,rotation,and multiple surface imbalance.Differences in Sagittal radiography parameters caused by genders is described in Fig. 4.For example,Vigdorchik et alfound that 204 cases (41%) of 500 patients with hip osteoarthritis had Low back pain, which may be caused by compensatory pelvic rotation in hip osteoarthritis,which may change the normal line of force of lumbar spine and induce low back pain [14] .However, the male pelvis is generally narrow and deep,and its line of force transmission is easy to affect the lower limb weightbearing axis,such as the femur side deformity of the male hip joint with acetabular syndrome,which damages the glenoid margin and articular cartilage [15] .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a global sagittal alignment using SVA alone fails to evaluate the compensatory actions of the pelvis and lower extremities [ 42 ]. The PT, which is a parameter of compensation in the pelvis and knee joints, should be considered together [ 43 , 44 ]. In addition, SVA is a parameter based on the posterior superior aspect of the sacrum rather than the hip axis, which is considered the important reference point for spinal balance, but SVA < 50 mm is recognized as one of the most important criteria for sagittal balance, which is equivalent to having the C7PL located posterior to the hip axis, and this threshold is consistent with a good HRQoL score [ 5 , 11 ].…”
Section: Spinopelvic Parametersmentioning
confidence: 99%
“…42 The PT, which is a parameter of compensation in the pelvis and knee joints, should be considered together. 43,44 In addition, SVA is a parameter based on the posterior superior aspect of the sacrum rather than the hip axis, which is considered the important reference point for spinal balance, but SVA < 50 mm is recognized as one of the most important criteria for sagittal balance, which is equivalent to having the C7PL located posterior to the hip axis, and this threshold is consistent with a good HRQoL score. 5,11 In radiologic measurements, angular parameters and ratios are preferred over distance parameters because they are less sensitive to changes in radiologic magnification.…”
Section: ) Sagittal Vertical Axismentioning
confidence: 99%